2008
DOI: 10.2134/jeq2007.0401
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Trends and Changing Agricultural Practices in a Midwest U.S. Watershed, 1994–2006

Abstract: Sediment and nutrient concentrations in surface water in agricultural regions are strongly influenced by agricultural activities. In the Corn Belt, recent changes in farm management practices are likely to affect water quality, yet there are few data on these linkages at the landscape scale. We report on trends in concentrations of N as ammonium (NH(4)) and nitrate (NO(3)), soluble reactive phosphorus (SRP), and suspended sediment (SS) in three Corn Belt streams with drainage areas of 12 to 129 km(2) for 1994 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 41 publications
2
87
2
Order By: Relevance
“…2) were indicative of degraded stream conditions throughout the study watershed. Nitrate concentrations at study sites generally exceeded summer values recently reported from streams in other row-crop dominated watersheds of the Midwestern U.S.A., where nitrate concentrations are consistently among the highest in the nation (Bernot et al, 2006;Figueroa-Nieves et al, 2006;Schilling and Spooner, 2006;Heatherly et al, 2007;Renwick et al, 2008;Wagner et al, 2008;Diebel and Vander Zanden, 2009;Warrner et al, 2009). Additionally, nitrate concentration at each of our study sites (range 5 5.6-29.0 mg/L) was higher than 3.2 mg/L, a threshold value that, based on a USEPA Wadeable Streams Assessment, is indicative of poor conditions in Midwestern streams (Van Sickle and Paulsen, 2008).…”
Section: Results Land Cover Stream Habitat and Invertebrate Assemblagescontrasting
confidence: 55%
“…2) were indicative of degraded stream conditions throughout the study watershed. Nitrate concentrations at study sites generally exceeded summer values recently reported from streams in other row-crop dominated watersheds of the Midwestern U.S.A., where nitrate concentrations are consistently among the highest in the nation (Bernot et al, 2006;Figueroa-Nieves et al, 2006;Schilling and Spooner, 2006;Heatherly et al, 2007;Renwick et al, 2008;Wagner et al, 2008;Diebel and Vander Zanden, 2009;Warrner et al, 2009). Additionally, nitrate concentration at each of our study sites (range 5 5.6-29.0 mg/L) was higher than 3.2 mg/L, a threshold value that, based on a USEPA Wadeable Streams Assessment, is indicative of poor conditions in Midwestern streams (Van Sickle and Paulsen, 2008).…”
Section: Results Land Cover Stream Habitat and Invertebrate Assemblagescontrasting
confidence: 55%
“…While necessary to feed and clothe a continually growing human population, these practices can often lead to significant soil erosion (Bennett and Chapline 1928) and surface runoff during rainfall events that produce increased loads of suspended sediment and dissolved solids, and decrease water clarity (Dodds and Whiles 2004;Renwick et al 2008). Despite decades of research and considerable efforts to mitigate suspended sediment loading, suspended sediment continues to be one of the most pernicious pollutants and a significant cause of water quality impairment globally.…”
mentioning
confidence: 99%
“…For the near term (perhaps one or more decades), given the low sedimentation rate at Cheney Reservoir, voluntary conservation practices in the basin may constitute an acceptable sediment management strategy. Use of conservation practices to minimize sediment runoff has been shown to decrease sediment delivery to streams and reservoirs (McIntyre 1993;Renwick et al 2005;Renwick et al 2008;Richards et al 2008) and prioritized implementation of such practices may further enhance the improvements realized (Legge et al 2013). Between 1994 and 2011, nontargeted best management practices were implemented at more than 1,000 sites in the Cheney Reservoir basin (Cheney Lake Watershed Incorporated, written communication, 2011).…”
Section: Yearmentioning
confidence: 99%